1997
DOI: 10.1002/(sici)1097-0290(19970205)53:3<296::aid-bit8>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecosystems in compost and granular activated carbon biofilters

Abstract: Compost and granular activated carbon biofilters operated at a wastewater treatment plant simultaneously removed low concentrations of hydrogen sulfide and volatile organic compounds. Through the use of phospholipid fatty acid analyses, the effects of declining pH caused by sulfide oxidation were established for microbial growth, microorganism stress, and microbial community structure. Microorganisms on both media demonstrated increases in microbial densities, varying degrees of environmental stress, and domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 10 publications
0
23
0
3
Order By: Relevance
“…The positive effect of the packing material (GAC) on degradation parameters and performance under fluctuating concentration has already been described for toluene, 16 -18 methyl ethyl ketone, 19 and odors and solvents. 20,21 In addition, the in-series reactor configuration used here may have resulted in better degradation ability of the mixed culture because of improved water supply and maintenance of the pH value in the individual reactor stages (bed heights). Figure 4 shows the RE across the individual stages of the biofilter (i.e., in different bed layers).…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect of the packing material (GAC) on degradation parameters and performance under fluctuating concentration has already been described for toluene, 16 -18 methyl ethyl ketone, 19 and odors and solvents. 20,21 In addition, the in-series reactor configuration used here may have resulted in better degradation ability of the mixed culture because of improved water supply and maintenance of the pH value in the individual reactor stages (bed heights). Figure 4 shows the RE across the individual stages of the biofilter (i.e., in different bed layers).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other studies (3), we observed a high spread of RSC inlet concentrations, which led to a high variability in RSC removal. Noticeable removal of RSCs started only Ϸ1 month after the system startup, indicating a slower growth and acclimation of the autotrophic/ heterotrophic mixed population degrading RSCs (23). This was most probably caused by the low concentrations of pollutant substrate and both kinetically and mass transfer-limiting conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Pulp and paper mill effluents are characterized by high COD and BOD levels. Webster et al (1997) have reported the inoculation of combined microorganisms, in which the degradation species was the survivor in the effluent treatment. If the native formulation is compared with the commercial formulation, and the native is the best, this indicates that the mixed culture is superior (Hurst et al 1997).…”
Section: Microbial Treatment Of Effluentmentioning
confidence: 99%